'A Walk down the Shore': A visual geography of ordinary violence in Istanbul. (December 2019) - Duru, Asli
In this paper, I examine where violence appears and how it is made sense of in Istanbul's everyday settings of construction and renewal. I develop a visual methodology and utilise ordinary violences as a framework to map fear and memories as extended human material. The discussion is based on a filmic iteration of audio-visual material on memories of violence interrogated through ways of doing and senses of belonging, security and use of space in Istanbul. I first discuss the differential routes to spatially exploring violence. Then, I present processes of visual research-creation in order to situate my argument on the emergent visibilities of violence. Next, I present textual layers of violence within immediate and networked settings of memory and emotions activated by Istanbul's everyday settings. Conclusion summarises the main argument on the liminal, 'barely visible' geographies of ordinary violence and the role of critical visual research in projecting improbable visibilities of restricted movement, under/hyper-exposed places and muted bodies.